Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12199-020-00891-4
|View full text |Cite
|
Sign up to set email alerts
|

An especial transition phase of hospitals: the adaptation of hospital operations to the development of COVID-19 and policy adjustments

Abstract: The ongoing pandemic coronavirus disease 19 (COVID-19) remains a significant issue for global health, economics, and society. In order to balance epidemic control and economic recovery, many countries have successively announced the gradual relaxation of some lockdown restrictions. Hospitals and medical staff constitute the backbone in this war against COVID-19. In response to this serious situation, many hospitals went into emergency and impaired healthcare access to patients with conditions other than COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…16,17 A large emerging body of literature on COVID-19 describes the negative impact of the pandemic on hospital operations, medical education, health screening and patient access to health care. [18][19][20][21][22] Importantly, the role of community pharmacists has shifted. Specifically, a qualitative study explored the role of Canadian pharmacists in providing care to patients with opioid use disorder (OUD) during the COVID-19 pandemic and found 3 major themes: optimization of opioid-related patient care, jurisdictional impact and awareness and education.…”
Section: Original Researchmentioning
confidence: 99%
“…16,17 A large emerging body of literature on COVID-19 describes the negative impact of the pandemic on hospital operations, medical education, health screening and patient access to health care. [18][19][20][21][22] Importantly, the role of community pharmacists has shifted. Specifically, a qualitative study explored the role of Canadian pharmacists in providing care to patients with opioid use disorder (OUD) during the COVID-19 pandemic and found 3 major themes: optimization of opioid-related patient care, jurisdictional impact and awareness and education.…”
Section: Original Researchmentioning
confidence: 99%
“…A study conducted in China concluded that in the initial phase of the COVID-19 pandemic in the country, the lack of efficient protective measures led to the emotional stress and psychological disturbance of the majority of the hospital staff; fortunately, the lessons they learned from such experiences helped them respond to the outbreak in later phases ( 6 ). Another study identified a need to adapt new modes of operation and to implement suitable modifications to patient care policies to deal with the challenges of this pandemic ( 7 ). Similar findings have been reported in a contemporary study, which concluded that (1) a multi-level and multidisciplinary approach by healthcare professionals and hospital administrators is needed toward the common goal of patient care, and (2) the protocols need revision on a regular basis to assure the best possible patient care ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hospitals’ management and operations have been disrupted and tested in this context. Some challenges include elevated patient volumes or increased risk profiles, risk of infection to caregivers and other patients, shortage of resources such as personal protective equipment (PPE), and lack of knowledge or coordination of resource availability ( Auerbach et al, 2020 ; Becker et al, 2021 ; Grigonis et al, 2021 ; Liu et al, 2020 ; Woolley et al, 2020 ). Auerbach et al (2020) report a potential risk of missed diagnoses of non-COVID-19 conditions in patients suspected with COVID-19 and missed COVID-19 diagnosis in patients admitted for non-respiratory reasons.…”
Section: Introductionmentioning
confidence: 99%